2014
DOI: 10.1089/scd.2013.0567
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cell Paracrine Activity Is Modulated by Platelet Lysate: Induction of an Inflammatory Response and Secretion of Factors Maintaining Macrophages in a Proinflammatory Phenotype

Abstract: Wound healing is achieved through distinct programmed phases: hemostasis, inflammation, mesenchymal cell proliferation and migration, and tissue remodeling. At the injury site, clot formation and platelet degranulation release cytokines and growth factors and actively participating in the healing process and regulating the migration of inflammatory cells, such as neutrophils, macrophages, and lymphocytes. We previously demonstrated that, in an inflammatory environment, prostaglandin E2 (PGE2) secreted by mesen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
65
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 38 publications
6
65
0
1
Order By: Relevance
“…All of these factors are known to increase during corneal wound healing 22. This is in agreement with several papers describing the upregulation of IL-6, IL-8, MCP-1 and RANTES (regulated on activation, normal T cell expressed and secreted)in MSCs 23. MCP-1 is a key chemokine involved in macrophage recruitment, whereas IL-6 and IL-8 play important roles in the regulation of leukocyte infiltration during the wound repair process.…”
Section: Discussionsupporting
confidence: 88%
“…All of these factors are known to increase during corneal wound healing 22. This is in agreement with several papers describing the upregulation of IL-6, IL-8, MCP-1 and RANTES (regulated on activation, normal T cell expressed and secreted)in MSCs 23. MCP-1 is a key chemokine involved in macrophage recruitment, whereas IL-6 and IL-8 play important roles in the regulation of leukocyte infiltration during the wound repair process.…”
Section: Discussionsupporting
confidence: 88%
“…Several studies have found that the exposure of MSCs to proinflammatory factors, sometimes for as little as a few hours, can alter the gene and protein expression of MSCs for days afterwards [52]. Factors known to be secreted or bound to MSC membranes with anti-inflammatory activities (activation of Tregs/tolerogenic dendritic cell phenotype; pro-resolving/M2 macrophage activation; inhibition or proapoptosis of T cells, B cells, NK cells, or dendritic cells; decreasing cytokine production) include: purines, bone morphogenetic proteins (BMPs, specifically BMP-4), CD274, CCL2, Connexin 43, cyclooxygenase (COX)/prostaglandin (PG), CD95/CD95 ligand, galectins, heme oxygenase-1, human leukocyte antigen-G (HLA-G), IDO/kynurenine, interleukin-6 (IL-6), leukemia inhibitory factor (LIF), NO, TGF-β, tumor necrosis factor-inducible gene-6 (TSG6), and vascular endothelial growth factor (VEGF) [53]. …”
Section: Mechanisms Of Msc Trophic Activitymentioning
confidence: 99%
“…MSCs have been the focus of intensive research efforts within the field of regenerative medicine: In various animal studies, MSCs were found to migrate to lesion sites and differentiate into tissuespecific functional cells [21][22][23]; they may also create a supporting microenvironment within organ damage by the secretion of cytokines, growth factors and other paracrine molecules, in turn supporting other cell types in the regeneration of tissue lesions [24][25][26][27][28]. To date, beneficial effects of MSCs regarding tissue damage have been most widely investigated for myocardial scars, cartilage and bone injuries, pulmonary damage, skin and nerve tissue lesions [29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%